Environmental impacts of forest biomass-to-energy conversion technologies: Grate furnace vs. fluidised bed furnace. (10th January 2018) - da Costa, Tamíris Pacheco; Quinteiro, Paula; Tarelho, Luís António da Cruz; Arroja, Luís; Dias, Ana Cláudia
Abstract: Electricity production from biomass has the potential to significantly contribute to the power mix in Portugal with lesser environmental impact than non-renewable resources. This study focuses on electricity production from the combustion of residual forest biomass from eucalypt logging activities in Portugal using life cycle assessment. In Portugal, several power plants fuelled by residual forest biomass have been commissioned in the last few years. Most of the installations use fluidised bed furnaces, and the others use grate furnaces. This study aims to compare the environmental impacts associated with these two alternative combustion technologies. System boundaries include the stages of forest management, collection processing and transportation and energy conversion. The default impact assessment method used is that suggested in the International Reference Life Cycle Data System. In a sensitivity analysis, calculations are performed using the ReCiPe method. For all of the impact categories analysed, the fluidised bed presents the smallest environmental impact. Even when the grate furnace efficiency increases and the fluidised bed efficiency decreases in the sensitivity analysis, the fluidised bed has lower impacts than the grate technology and can be the best alternative in the implementation of new power plants.